Blockchain in logistics and supply chain: Trick or treat? - Niels Hackius; Moritz Petersen (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Blockchain is an emergent technology concept that enables the decentralized and immutable storage of verified data. Over the last few years, it has increasingly attracted the attention of different industries. Especially in Fintech, Blockchain is hyped as the silver bullet that might overthrow today's payment handling. Slowly, the logistics and supply chain management community realizes how profoundly Blockchain could affect their industry. To shed light on this emerging field, we conducted an online survey and asked logistics professionals for their opinion on use case exemplars, barriers, facilitators, and the general prospects of Blockchain in logistics and supply chain management. We found most of our participants are fairly positive about this new technology and the benefits it offers. However, factors like the hierarchical level, Blockchain experiences, and the industry sector have a significant impact on the participants' evaluation. We reason that the benefits over existing IT solutions must be carved out more carefully and use cases must be further explored to get a rather conservative industry, like logistics, more excited about Blockchain.
urn:nbn:de:gbv:830-88217327; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; Blockchain; logistics; supply chain management; use cases